2008
DOI: 10.4049/jimmunol.180.6.4283
|View full text |Cite
|
Sign up to set email alerts
|

Protective Roles of the Fractalkine/CX3CL1-CX3CR1 Interactions in Alkali-Induced Corneal Neovascularization through Enhanced Antiangiogenic Factor Expression

Abstract: Macrophage infiltration is observed during the course of corneal neovascularization. We examined corneal neovascularization process after alkali injury in mice deficient in fractalkine receptor/CX3CR1, which is expressed by macrophages. The mRNA expression of CX3CR1 and its ligand CX3CL1/fractalkine was augmented together in the corneas after alkali injury. Compared with WT mice, CX3CR1‐deficient (KO) mice exhibited enhanced corneal neovascularization 2 weeks after injury, as evidenced by enlarged CD31‐positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 54 publications
3
68
0
Order By: Relevance
“…The male CX3CR1-deficient mice were on an outbred C57BL/6 genetic background (n48 generations), and were used at 30 weeks of age. 9,10 Five mice were used in each experiment. All animal experiments were performed at the Institute for Experimental Animals (Kanazawa University Advanced Science Research Center, Kanazawa, Japan), complied with the standards set out in the Guidelines for the Care and Use of Laboratory Animals of Kanazawa University, and were approved by the Committee on Animal Experimentation of Kanazawa University.…”
Section: Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The male CX3CR1-deficient mice were on an outbred C57BL/6 genetic background (n48 generations), and were used at 30 weeks of age. 9,10 Five mice were used in each experiment. All animal experiments were performed at the Institute for Experimental Animals (Kanazawa University Advanced Science Research Center, Kanazawa, Japan), complied with the standards set out in the Guidelines for the Care and Use of Laboratory Animals of Kanazawa University, and were approved by the Committee on Animal Experimentation of Kanazawa University.…”
Section: Methods Animalsmentioning
confidence: 99%
“…8 Recently, pathophysiological roles of the fractalkine-CX3CR1 axis were noted in the bactericidal host defense during septic peritonitis 9 and corneal neovascularization. 10 Additionally, fractalkine/CX3CL1 was reported to be involved in the progression of human glomerulopathy, including crescentic glomerulonephritis. 11 Collectively, these data suggest that the fractalkine-CX3CR1 axis may promote tissue injury through immune competent cell infiltration and fibrogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…1C). Since macrophages are a major source of MMP12, it is interesting that the high expression levels of Mmp12 noted at 2 and 6 days after injury corresponded with time points of high macrophage recruitment (Lu et al, 2008;Nakao et al, 2005). Since resident macrophages are normally present in the cornea (Brissette-Storkus et al, 2002), we determined their ability to express Mmp12.…”
Section: Mmp12 Is Expressed During Corneal Wound Healingmentioning
confidence: 99%
“…6 Although there is considerable evidence that macrophages are proangiogenic, [7][8][9][10][11] recent studies suggest that macrophages may be antiangiogenic. 12,13 Furthermore, the dichotomy of monocytes/ macrophages has been proposed based on their expression levels of CCR2 and CX3CR1. [14][15][16][17][18] We recently revealed that infiltrating CX3CR1-positive macrophages were protective for alkali-induced corneal neovascularization through antiangiogenic molecule expression.…”
mentioning
confidence: 99%